THE NEED ANALYSIS OF WRITING MODULE WITH EDMODO - Yanti Juniarti; Subadiyono Subadiyono; Zahra Alwi (University of Kuningan, 2021)
Paper writing skills for Akamigas Polytechnic Students Palembang had not reached the expectation. They still had difficulties organizing the ideas into written forms and effective sentences. They did not understand the paper writing systematically, how to cite, and how to write the bibliography. They were caused by the use of limited teaching materials, by relying on PowerPoint as the main media. This research aimed to find out what the students needed of Edmodo-writing module. This research is a part of the identification of teaching material needs to explore the needs of the teaching materials. Therefore, this research applied the qualitative approach with descriptive method. The data were collected with a closed-questionnaire and interview. The need analysis showed a percentage of 97.1% of students preferred the Internet as the reference source to any other. Therefore, it is important to technology-based learning media that provided several applications. They could facilitate both lecturer and students to share and to learn the materials. The data showed 87.1% of students needed technology-based teaching materials, such as Edmodo. A percentage of 91.4% of students stated that they wanted technology-based teaching materials that were developed into modules assisted with Edmodo. Besides that, a percentage of 95.7% of students wanted guidelines to facilitate them applying the module and using the Edmodo.